Pre-speech diagnosis in hearing-impaired infants: How auditory experience affects early vocal development. (1st June 2013) - Shehata-Dieler, Wafaa; Ehrmann-Mueller, Desiree; Wermke, Peter; Voit, Verena; Cebulla, Mario; Wermke, Kathleen
<x xml:space="preserve">Abstract</x> Using frequent recordings of spontaneous vocalizations from cooing to word production and applying signal analysis methods, we aimed to objectively determine the developmental pre-speech profiles of young hearing-impaired infants with regard to the duration of auditory deprivation and the benefit accrued from hearing aids. The assessment of the benefit from amplification of the hearing level in infants is limited to subjective observation. In this pilot study, we aimed to demonstrate the advantage of an objective fine-grained analysis in three representative infants with similar audiological findings but different early auditory experience. The infants were born with profound hearing loss and aided at different ages within 6 months after birth. Spectral analysis and formant analysis of more than 11 000 vocalizations were performed. This allowed for a reliable identification of the time points at which each infant reached the early vocal stages. The analysis demonstrated that individual developmental courses from cooing to word production varied depending on the duration of early auditory deprivation. The findings suggest that inadequate auditory input affects infants' vocal development long before the stage of first speech-like vocalizations (canonical babbling). Pre-speech diagnosis as introduced here may offer an additional objective tool in the diagnosis of hearing impairment in pre-lexical infants and in the assessment of the benefit of amplification.